FGD dan Pelatihan untuk Inventarisasi, Perencanaan dan Pemantauan Ekosistem Gambut Terhadap Anggota Tim Penyusun RPPEG di Kabupaten Aceh Barat dan Nagan Raya - Mursyidin Mursyidin; Riza Hasan; Rahmad Nuthihar; M. Faisi Ikhwali; Indrianto Indrianto; Andrisman Satria (Universitas Teuku Umar, 2023)
This paper details the report of the Focus Group Discussion (FGD) and Training on Inventory, Planning, and Monitoring of Peat Ecosystems in the districts of West Aceh and Nagan Raya held in October 2023. The activities involved lecturers from Universitas Malikussaleh, AKN Aceh Barat, UIN Ar-Raniry Banda Aceh, and the Sustainable Ecosystem Foundation (YEL), with the aim of formulating the Plan for the Protection and Management of Peat Ecosystems (RPPEG). Through the FGD, a deep understanding of the complexity of peat ecosystem management was achieved, with the identification of challenges such as land use change. The technical training included GIS mapping and peat depth measurements, enhancing the skills of the RPPEG drafting team. With a strong legal foundation and involving multiple stakeholders, this report becomes a strategic basis for the RPPEG in West Aceh and Nagan Raya. These steps encompass the protection of local communities, creating an inspirational model for other regions in managing peat ecosystems in accordance with sustainability principles and environmental regulations.